The Role of Multicultural Marketing on Malay Consumers Perceptions towards Global vs. Local Ethnic Food Brands - Umair, Sana (2013)
This dissertation combines two different elements of interest in International Marketing Research. The objective of this research is the comparison of global versus local brand within the context of ethnic marketing in the multicultural society of Malaysia. The product instant noodle in the category of ethnic food was chosen in the variant of Asam Laksa as the target sample focused specifically on Malay consumers. Comparison was done between Maggi (global) and Mamee (local). The sample comprised of 200 respondents in Kajang and Kuala Lumpur district regions of Klang Valley district in Selangor. Data was examined using MANOVA the procedure of multivariate analysis of variance (MANOVA) followed by independent samples t test to measure group differences between the two brands based on moderating factors of consumer ethnocentrism, strength of ethnic identity and self-reference. The MANOVA results revealed that there was no significant interaction between the advertisements of these brands and the three moderating factors. Analysis done on group differences suggested that Malay consumers the global brand Maggi in higher esteem as mean scores for brand image, emotional value, brand loyalty and purchase were all higher. Ethnocentrism was seen to play a role to only a certain extent since product was low in consumer involvement. Interestingly so, there was no radical impact of strength of ethnic identity and self-reference in consumer decision making process for choosing the brands.